Wydatki inwestycyjne gmin wiejskich przed integracją i po integracji z Unią Europejską - Krukowski, Krzysztof (Investment Expenditure of Rural Communes Before and after the Accession with the European Union, 2005)
Poland's accession to the European Union made rural communes benefiting from the European Research Development Fund precise planning of investments. Planned investment expenditure by one inhabitant in the surveyed communes will increase three times in 2004-2013, which positively testifies to European funds influence in the area of investment expenditure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 508-512